Development of Microstructure on Titanium Implant Surface Using CO2 Laser Processing (Mustansiria Dental Journal, 2024)
Background: Dental biomaterials made of titanium are commonly used. It depends on the implant surface texture to improve fixation and prevent the unwanted adhesion of bone cells. This study aimed to investigate whether continuous laser beam carbon dioxide (CNC - CO2) lasers produce specific textures on titanium surfaces with micrometer-sized indentations that influence cell behavior. Materials and method: (CNC - CO2) red laser device; with a fundamental wavelength of λ=10600 nm and power pulses of 34 W were applied, and textures on the surface of titanium discs were achieved.  Results: Excellent degrees of uniformity and repeatability were achieved for the desired portions of the surface by creating different surface textures. The surface topography and chemical composition of the specimens were investigated by scanning electron microscopy, electron dispersive spectroscopy, X-ray diffraction, and surface roughness measurements. Also, a laser power of 34 watts raised the surface roughness, Ra (1.71 nm), and Rz (1.99 nm). Conclusion: Titanium surface textures with unique qualities can be formed in response to an increased heat input. When excessive laser power was used, the measured roughness increased because of instantaneous re-melting. The use of a right continuous-wave (CNC - CO2) laser on titanium used in dental implants can form specific surface textures.